2014
DOI: 10.1111/apt.12866
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical study: comparison of acceptability, patient tolerance, cardiac stress and endoscopic views in transnasal and transoral endoscopy under local anaesthetic

Abstract: SUMMARY BackgroundTransnasal endoscopy (TNE) with ultrathin endoscopes has been advocated as an attractive alternative, for diagnostic upper endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Stroppa et al 21 conducted a comparative study in which patients were submitted to 2 exams on different days, TNE (without sedation) or EGD (under sedation). The authors reported that 87 % of their patients also preferred TNE, similar to data from other studies 22 23 . …”
Section: Resultssupporting
confidence: 84%
“…Stroppa et al 21 conducted a comparative study in which patients were submitted to 2 exams on different days, TNE (without sedation) or EGD (under sedation). The authors reported that 87 % of their patients also preferred TNE, similar to data from other studies 22 23 . …”
Section: Resultssupporting
confidence: 84%
“…The assessment of cardiac function and oxygen saturation are both objective methods of evaluating safety and tolerability of endoscopic procedures. Previous studies have shown that TNE causes fewer adverse effects on cardiovascular function than transoral OGD 36 40 41. It is also less stressful to the cardiovascular system with reduced elevation of systolic blood pressure and less sympathetic stimulation than the oral procedure 41.…”
Section: Patient Tolerability Side Effects and Safetymentioning
confidence: 99%
“…Previous studies have attempted to quantify hemodynamic shifts during TNFE in both laryngeal and esophageal procedures . In the field of otolaryngology, two specific studies have laid the groundwork for this investigation …”
Section: Introductionmentioning
confidence: 99%